2021
DOI: 10.1371/journal.pone.0257782
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of utilization of antenatal and delivery care at the community level in rural Bangladesh

Abstract: Background Timely utilization of antenatal care and delivery services supports the health of mothers and babies. Few studies exist on the utilization and determinants of timely ANC and use of different types of health facilities at the community level in Bangladesh. This study aims to assess the utilization, timeliness of, and socio-demographic determinants of antenatal and delivery care services in two sub-districts in Bangladesh. Methods This cross-sectional study used data collected through a structured q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 41 publications
(46 reference statements)
11
21
1
Order By: Relevance
“…Women had given born one or more children had moreaccess problems than those who do not give birth. The nding of the study is in line with the study done in Bangladesh (22). The possible reason might be women who gave birth at health facilities may face unsatisfactory experiences which hinders them from accessing health care services (23).…”
Section: Discussionsupporting
confidence: 77%
“…Women had given born one or more children had moreaccess problems than those who do not give birth. The nding of the study is in line with the study done in Bangladesh (22). The possible reason might be women who gave birth at health facilities may face unsatisfactory experiences which hinders them from accessing health care services (23).…”
Section: Discussionsupporting
confidence: 77%
“…A retrospective study using data from the Health and Demographic Surveillance System (HDDS) in Matlab, Bangladesh, discovered that cesarean delivery increased with greater socioeconomic status, education, and utilization of antenatal care services [ 25 ]. Another study conducted in Bangladesh confirmed the significance of socio-demographic variables in the use of ANC and facility delivery [ 26 ].…”
Section: Discussionmentioning
confidence: 93%
“…Mothers are getting more antenatal care from private facilities in Bangladesh than ever. 13 Therefore, the business-oriented approaches of some private hospitals/clinics and physicians are indirectly provoking to increase C-section deliveries in Bangladesh. 14 , 15…”
Section: Prevalence and Associated Factors For C-sections In Bangladeshmentioning
confidence: 99%